The Effects of Different Doses of Alfentanil and Dexmedetomidine on Prevention of Emergence Agitation in Pediatric Tonsillectomy and Adenoidectomy Surgery - Zhang, Yan-zhuo; Wei, Xiong-li; Tang, Bin; Qin, Yuan-yuan; Ou, Min; Jiang, Xiao-hong; Tan, Yu-feng; Ye, Mao-ying (Frontiers in Pharmacology, 2022)
Background: Emergence agitation (EA) is a common problem often observed in children after sevoflurane anesthesia, which can be prevented by dexmedetomidine and Alfentanil. This study aims to compare the effectiveness of dexmedetomidine alone and with different doses of Alfentanil in preventing EA in children under sevoflurane anesthesia. Materials and Methods: In a double-blind trial, 80 children (ASA I or II, 3-7 years old) undergoing tonsillectomy and adenotonsillectomy with sevoflurane anesthesia were randomly assigned into four groups: control group; dexmedetomidine (DEX) group; dexmedetomidine plus 10μg/kg alfentanil group (DEX+Alf1); dexmedetomidine plus 20μg/kg alfentanil group (DEX+ALf2). The incidence of EA was assessed with the Aono’s scale and the severity of EA was evaluated with the pediatric anesthesia emergence delirium (PAED) scale. Time of tracheal extubation and time of awake were recorded. Postoperative pain and complication such as nausea and vomiting, cough, laryngospasm, bradycardia were recorded. Results: The incidence of EA was 50% in the control group, 25% in the DEX group, 5% in the DEX+Alf1 group. And it never happened in the DEX+Alf2 group. The Aono’s scale, the PAED scale and the FLACC scale in the control group and the DEX group were significantly more than those in the DEX+Alf1 group and the DEX+Alf2 group after the tracheal extubation (P < 0.05). The time of tracheal extubation of the control group and the DEX group were significantly shorter than those in the DEX+Alf1 group and the DEX+Alf2 group (P < 0.05). The awakening time of the DEX+Alf2 group is significantly longer than those in other groups (P < 0.05). The case of postoperative nausea and vomiting in the DEX+Alf1 group was fewer than those in the other group (P < 0.05). Conclusions: The combined administration of alfentanil and dexmedetomidine can reduce EA in children undergoing tonsillectomy alone and adenotonsillectomy with sevoflurane anesthesia. Dexmedetomidine plus 10μg/kg alfentanil seems to be more appropriate than other dose combinations as it reduced EA and postoperative nausea and vomiting but did not prolong the time to awake.